EFFECT OF IMPURITIES ON GRAIN GROWTH IN COLD ICE SHEETS - Durand G.; Weiss J.; Barnola J.M.; Krinner G.; Parrenin F.; Delmonte B.; Ritz C.; Duval P.; Bigler M.; Lipenkov V.; Röthlisberger R. (My University, 2006)
On the basis of a detailed study of the ice microstructure of the European Project for Ice Coring in Antarctica (EPICA) ice core at Dome Concordia, Antarctica, we analyze the effect of impurities (solubles, and insolubles, that is, dust particles) on the grain growth process in cold ice sheets. As a general trend, the average grain size increases with depth. This global increase, induced by the normal grain growth process, is punctuated by several sharp decreases that can be associated with glacial-interglacial climatic transitions. To explain the modifications of the microstructure with climatic changes, we discuss the role of soluble and insoluble impurities on the gram growth process, coupled with an analysis of the pinning of grain boundaries by microparticles. Our data indicate that high soluble impurity content does not necessarily imply a slowdown of grain growth kinetics, whereas the pinning of grain boundaries by dust explains all the observed modifications of the microstructure. We propose a numerical model of the evolution of the average grain size in deep ice cores that takes into account recrystallization processes such as normal grain growth and rotation recrystallization as well as the pinning effect induced by dust particles, bubbles, and clathrates on the grain boundaries. Applied to the first 2135 m of the Dome Concordia core, the model reproduces accurately the measured mean grain radius. This indicates a major role of dust in the modification of polar ice microstructure and shows that the average grain size is not a true paleothermometer, as it is correlated with climatic transitions through the dust content of the ice. Copyright 2006 by the American Geophysical Union.